The influence of immunoglobulin class G from blood plasma of patients with stroke on the activity of some parameters of hemostasis system. Issue 8 (December 2016) - Katrii, Tetiana B.; Kravchenko, Natalia K.; Vovk, Tetiana B.; Savchuk, Olexiy M.; Ostapchenko, Ludmila I.
Abstract : Today, cardiovascular diseases are one of the main causes of disability of the population. Most of the illnesses, including stroke, are accompanied by the appearance immunoglobulin G (IgG) in the blood circulation. According to the literature sources and previous experiments, it is known that IgG made influence on the hemostasis system. Objectives of the investigation are pure enzymes: thrombin, factor X, proenzyme of protein C and prothrombin under the influence of IgG fraction that were separated from the plasma of patients with atherothrombotic and cardioembolic ischemic stroke and patients with other neurological diseases. IgG was separated by affinity chromatography. Disc electrophoresis was used to control antibodies' purity. The main goal of the experiment is to test the potential influence of all fractions of separated IgG on the process of hydrolysis of specific chromogenic substrates by the key factors of the hemostasis system such as thrombin, factor X and protein C. The appearance of IgG in the blood stream during the atherothrombotic and cardioembolic ischemic stroke and other neurological diseases was proved. Concentration of the IgG in plasma of patients with cardioembolic ischemic stroke was significantly higher compared with healthy donors, whereas the IgG in plasma of patients with atherothrombotic ischemic stroke and other neurological disorders was not significantly different. Their potential ability to influence the enzymes such as thrombin, factor X, proenzyme of protein C and prothrombin was shown. It was proved that the antibody fractions of all experimental groups significantly accelerate the process of splitting chromogenic substrate by thrombin but inhibited cleavage of a specific chromogenic substrate by protein C.